The Continuous Classical Optimal Control Problems for Triple Nonlinear Elliptic Boundary Value Problem - Al-Hawasy, Jamil A.; Jasim, Doaa Kateb (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this research, our aim is to study the optimal control problem (OCP) for triple nonlinear elliptic boundary value problem (TNLEBVP). The Mint-Browder theorem is used to prove the existence and uniqueness theorem of the solution of the state vector for fixed control vector. The existence theorem for the triple continuous classical optimal control vector (TCCOCV) related to the TNLEBVP is also proved. After studying the existence of a unique solution for the triple adjoint equations (TAEqs) related to the triple of the state equations, we derive The FrÃ©chet derivative (FD) of the cost function using Hamiltonian function. Then the theorems of necessity conditions and the sufficient condition for optimality of the constraints problem are proved